Son of Paleface - Tashlin, Frank; Hope, Bob, 1903-2003.; Russell, Jane, 1921-2011.; Rogers, Roy, 1911-1998.; Williams, Bill, 1915-1992.; Paramount Pictures Corporation; Brentwood Home Video (Firm) (Newbury Park, CA : Brentwood Home Video, 2000)
A man heads out west to claim his fathers inheritance, and teams up with a cowboy and his horse to get to the bottom of a gold shipment robbery. An attractive female outlaw must save the hapless hero along the way.
Videodisc release of the 1952 motion picture.
Interactive menus, scene access, Bob Hope biography/filmography, audio: Dolby digital mono.
Producer, Robert L. Welch; screenplay, Frank Tashlin, Robert L. Welch, Joseph Quinlan; director of photography, Harry J. Wild; art direction, Hal Pereira, Roland Anderson; editor, Eda Warren; score, Lyn Murray; songs, Jay Livingston and Ray Evans, Jack Brooks, Jack Hope and Lyle Moraine.
Bob Hope, Jane Russell, Roy Rogers, Trigger, Bill Williams.
DVD.
Keywords: Musical films; Western films; Comedy films; Feature films